2004
DOI: 10.1016/s0002-9440(10)63096-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ubiquitin Carboxy Terminal Hydrolase-L1 in Neural Cell Apoptosis Induced by Ischemic Retinal Injury in Vivo

Abstract: Ubiquitin is thought to be a stress protein that plays an important role in protecting cells under stress conditions; however, its precise role is unclear. Ubiquitin expression level is controlled by the balance of ubiquitinating and deubiquitinating enzymes. To investigate the function of deubiquitinating enzymes on ischemia-induced neural cell apoptosis in vivo, we analyzed gracile axonal dystrophy (gad) mice with an exon deletion for ubiquitin carboxy terminal hydrolase-L1 (UCH-L1), a neuron-specific deubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 51 publications
(63 reference statements)
7
63
0
3
Order By: Relevance
“…With regard to cryptorchid injury, the balance between the expression of apoptosis-protecting and apoptosisinducing proteins constitutes one possible mechanism underlying the observed germ cell protection and apoptosis from apoptosis in gad and Uchl3 knockout mice, respectively. In gad mice, cryptorchid injury caused a large increase in the antiapoptotic proteins Bcl-2, Bcl-xL and XIAP, a result which was consistent with a previous report using retina [9]. In addition, the expression levels of the prosurvival proteins pCREB and BDNF also increased in gad mice.…”
Section: Uch-l1 and Uch-l3 Are Reciprocal Modulators Of Germ Cell Aposupporting
confidence: 91%
“…With regard to cryptorchid injury, the balance between the expression of apoptosis-protecting and apoptosisinducing proteins constitutes one possible mechanism underlying the observed germ cell protection and apoptosis from apoptosis in gad and Uchl3 knockout mice, respectively. In gad mice, cryptorchid injury caused a large increase in the antiapoptotic proteins Bcl-2, Bcl-xL and XIAP, a result which was consistent with a previous report using retina [9]. In addition, the expression levels of the prosurvival proteins pCREB and BDNF also increased in gad mice.…”
Section: Uch-l1 and Uch-l3 Are Reciprocal Modulators Of Germ Cell Aposupporting
confidence: 91%
“…Bonin et al 39 found that prosurvival protein BDNF was importantly downregulated in whole mouse brains of young GAD mice lacking UCH-L1. In contrast, Harada et al 40 showed that the levels of antiapoptotic proteins Bcl-2, XIAP and BDNF were increased in retinal cells of GAD mice reducing apoptosis. All these data suggest that the molecular responses for UCH-L1 deficiency are celltype and tissue-type specific and can result in both increased and decreased apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…The other stress-related protein that was more abundant in the hypothalamus of mice subjected to microgravity was ubiquitin carboxy-terminal hydrolase L1 (UCLH-1) (Spot 5). UCH-L1 is thought to regulate ubiquitin hydrolysis of larger ubiquitin conjugates after stress stimuli; ubiquitin in turn is thought to be a stress protein that plays an important role in protecting cells under stress conditions [18]. Peroxiredoxin (PRX) (Spot 6) is an antioxidant protein that plays a critical role in protecting against endogenously produced peroxides in both prokaryotes and eukaryotes.…”
Section: Resultsmentioning
confidence: 99%